ANALISIS TINGKAT PENGHASILAN PEGAWAI NEGERI SIPIL PADA PERGURUAN TINGGI NEGERI DI KOTA MAKASSAR - Andi Asrul; I Made Benyamin; Muh Jibril Tajibu (AkMen JURNAL ILMIAH, 2018)
The aims of this this research were to determine the influence of family dependents, age, education, health, gender and leissure time on the level of income through human capital investment.This research uses the primary data. Sampling method was done by Slovin so that the samples obtained by 244 respondents. The analytical method used is Two Stage Least Square. The results showed that dependents of family, age had a negative effect on the income level of civil servantsthrough human capital investment. While education, sex had a positive effect on the income level of civil servantsthrough human capital investment. While, health and leissure time does not effect the level of civil servant income through human capital investment in Makassar.